Cationic closo-carboranes 2. Do computed 11B and 13C NMR chemical shifts support their experimental availability? - Hnyk, Drahomír; Jayasree, Elambalassery G (Journal of computational chemistry, 2013)
(11)B and (13)C NMR spectra of so-far experimentally unknown carbon-rich cationic closo-carboranes C(3)B(n-3)H(n)(+) (n = 5, 6, 7, 10, 12) have been calculated at the GIAO-MP2 level and subsequently analyzed to reveal the nature of bonding in these potentially weakly coordinating cations. All previous rules derived for understanding (11)B NMR spectra of borane derivatives can be applied to realistically account for the corresponding shieldings. The correlated wavefunction for n = 5 and, to a lesser extent, for n = 10 seems to be decisive when trying to compute realistic shielding tensors, which is in agreement with the corresponding known dicarbaboranes. For other cluster dimensions noncorrelated wavefunctions also work well, in particular in relation to the corresponding dicarbaboranes. All these observations strongly support the fact that experimental availability of these unique clusters is possible.